The glycolytic pathway is a target for drug discovery against tropical diseases - Ahmad Fuad, Fazia Adyani; Tanbin, Suriyea; Ogu Salim, Nurhainis (2022)
Glycolysis is the heart of various metabolic processes, ranging from energy generation to biosynthesis of molecules, indicating its importance as the most primeval metabolic pathway in nearly all living organisms. The pathway has also been perceived as an energy provider for viral replication, which has been previously shown to be altered upon virus infection. Here, we discuss the potential role of glycolysis as a target for the discovery of new drugs against infectious tropical diseases, such as malaria and dengue. Compounds that may possess the ability to inhibit some of the enzymes in the glycolytic pathway, such as lactate dehydrogenase (LDH) and hexokinase isoform 2 (HK2) were initially screened through virtual means, prior to the production of these enzymes in the bacterial system. The effects of these potential inhibitors on the activity of the enzymes were subsequently evaluated, by benchmarking with known inhibitors of these enzymes. Some of the virtually screened compounds, notably Chitin, an analogue of a known inhibitor of human HK2, 2- deoxyglucose (2-DG), exhibited substantial inhibition on the enzyme’s activity, which indicates its potential to disrupt dengue virus (DENV) replication. Meanwhile, oxalic acid, which is an analogue of a known inhibitor of LDH, oxamate, has shown promising inhibition on the activity of Plasmodium knowlesi LDH (Pk-LDH), also indicating the possibility of the virtually screened compound to be developed into a potent drug that specifically targets the enzyme. These initial works may provide future explorative potential and have paved the path towards the discovery of new drugs for the treatment of tropical infectious diseases.